Prediction of Sentiment from Macaronic Reviews (Informatica, 2018)
Language used by people in the online content has not any proper format. For their own convenience, they also use some native language words while writing anything online i.e. reviews, blogs, etc. The presence of native words along with base language is known as macaronic language. The use of macaronic languages is on the rise these days. It also facilitates the need of expert analysers for the processing of such content to take effective decisions. The performance of various decision support systems is dependable over these analysers. Therefore, in this paper, an algorithm is developed which is a hybridised algorithm which first normalize the content to its base language later sentiment analysis is performed over it. The experimental results using proposed algorithm indicates a trade-off between various performance aspects.Computer